The association of E2F1 and E2F2 single nucleotide polymorphisms with laryngeal squamous cell carcinoma pathomorphological features - Tomas Jakstas; Agne Bartnykaite; Evaldas Padervinskis; Aurelija Vegiene; Elona Juozaityte; Virgilijus Uloza; Rasa Ugenskiene (BMC Cancer, 2024)
Abstract Background Laryngeal squamous cell carcinoma (LSCC) is one of the most common types of cancer in the upper respiratory tract. It is well-known that it has a high mortality rate and poor prognosis in advanced stages. There are well-known risk factors for LSCC, though new specific and prognostic blood-based markers for LSCC development and prognosis are essential. The current study aimed to evaluate the impact of four different single nucleotide polymorphisms (SNPs), E2F1 (rs3213183 and rs3213180) and E2F2 (rs2075993 and rs3820028), on LSCC development, morphological features, and patient 5-year survival rate. Methods A total of 200 LSCC patients and 200 controls were included in this study; both groups were matched by age and sex. In the present study, we analyzed four single nucleotide polymorphisms (SNPs) in the genes E2F1 (rs3213183 and rs3213180) and E2F2 (rs2075993 and rs3820028) and evaluated their associations with the risk of LSCC development, its clinical and morphological manifestation, and patients 5-year survival rate. Genotyping was carried out using RT-PCR. Results None of the analyzed SNPs showed a direct association with LSCC development. E2F2 rs2075993 G allele carriers (OR = 4.589, 95% CI 1.050-20.051, p = 0.043) and rs3820028 A allele carriers (OR = 4.750, 95% CI 1.088–20.736, p = 0.038) had a statistically significantly higher risk for poor differentiated or undifferentiated LSCC than non-carriers. E2F1 rs3213180 GC heterozygotes were found to have a 3.7-fold increased risk for lymph node involvement (OR = 3.710, 95% CI 1.452–9.479, p = 0.006). There was no statistically significant association between investigated SNPs and patient 5-year survival rate. Conclusions The present study indicates that E2F2 rs2075993 and rs3820028 impact LSCC differentiation, whereas E2F1 rs3213180 - on lymph node involvement.